STUDI PERMAINAN BISIK BERANTAI DALAM PENGEMBANGAN BAHASA ANAK USIA DINI - Ike Lovita; Syahrul Ismet (JCE (Journal of Childhood Education), 2021)
This study aims to see how chain whispering plays in early childhood language development. The sub-focus of this research are: 1) whisper game material in early childhood language development, 2) the steps of serial whispering games, 3) the benefits of chain whispering games in early childhood language development, 4) language skills developed in chain whisper games . The research method used a qualitative literature study method. Sources of research data use scientific articles, books, and other sources. Techniques to study data are literature that is relevant to the object referred to in discussion. The results showed several findings from the sub-focus: 1) the material for developing the language of children through serial whispering games could be forming sentences, sentences that are quite long,everyday sentences, formal sentences. 2) the steps of the whispered chain game as follows the teacher forms a group, the child receives a message from the teacher, the first player receives the message and so on, the last player concludes. 3) the benefits of this game are as follow increase vocabulary, communicate appropriately and correctly, 4) language skills developed through serial whisper games are: speaking skills, listening skills, listening skills.